Predicting the Behaviour of Fibre Reinforced Cement Treated Clay. (2016) - Nguyen, Lam; Fatahi, Behzad; Khabbaz, Hadi
Abstract: Treating soft clay with cement and fibre has become an effective ground improvement technique for transport infrastructure. Application of recycled fibres in deep soil mixing columns in soft soil sections of road and rail projects is being considered by designers and clients as an efficient technique. However, the combined effect of cement and fibre at failure requires further investigation. As the effective stresses increase to a sufficiently high stress, the effect of cementation is diminished due to the degradation of cementation bonds and the fibre exhibits failure due to either complete pull-out or breakage from the soil matrix. Thus, the failure envelope of the reinforced soil gradually merges with that of un-reinforced soil at higher stresses. In this paper, a constitutive model is proposed to simulate the behaviour of the cement treated-fibre reinforced soil based on the Critical State Soil Mechanic and the Modified Cam Clay model. In particular, the proposed model captures the beneficial effects of cementation and fibre reinforcement such as the improvement in strength and ductility while the cementation degradation and the failure mechanism of the fibre are also considered. In addition, a series of un-drained triaxial tests were conducted to verify the performance of the proposed model. This paper concludes that adding fibre into the cement treated soil clearly improves its residual strength, thus, a significant increase in ductility is observed and well simulated. In this study, by modifying the mean effective stress to include the cementation degradation and the fibre failure mechanism, the proposed model results in realistic prediction for the behaviour of soil treated with cement and fibre.